Fabrication and characterization of polyaniline/multi walled carbon nanotube conjugated with doxorubicin for optical and morphological properties - C.R BISWAL; KAMPAL MISHRA; PADMOLOCHAN NAYAK (International Journal of Pharma and Bio Sciences, 2017)
Today nanotechnology is created a new revolution in research. Multi walled carbon nanotube (MWCNT) has multifunctional properties which can be used for different purpose. In our research, we have focused to prepare functionalized MWCNT and study potentiality of f-MWCNT based conjugating materials for biomedical application. In the present study, acid functionalized multiwalled carbon nanotube (f-MWCNT) grafted with polyaniline (PANI) then further f-MWCNT/PANI is subsequently conjugated with anticancer drug doxorubicin (DOX). We have characterized the structure of synthesized f-MWCNT/ PANI-DOX composites by UV-Visible spectrophotometer, X-ray diffraction pattern (XRD), scanning electron microscopy (SEM) and particle size analyzer. In UV-Visible spectrophotometer was given successful result of conjugation in between DOX, PANI and f-MWCNT. The shifting peak was conformed of conjugation. XRD data was suggested the strongly crystalline physical character and well conjugated with anticancer drug doxorubicin into f-MWCNT/PANI surfaces. This experiment may be very useful for drug delivery and biosensor purpose with different type of biomedical applications.